Perspective of high school students in intergrated mathematics with technology post pandemic covid-19 - Akbar, Muhammad Rifqi; Umam, Khoerul (International Journal of Trends in Mathematics Education Research, 2023)
The COVID-19 pandemic has changed the landscape of education around the world, including learning mathematics at the high school level. In response to the pandemic, many schools have adopted distance learning and integrated technology into the learning process. This study aims to analyze the perspectives of high school students in learning mathematics that is integrated with technology after the COVID-19 pandemic. In this context, we will explore students' understanding of the use of technology in learning mathematics, their attitudes towards the use of technology, and their views on the effectiveness of learning mathematics integrated with technology. The research method used in this study is a quantitative research method with the type of research used in this study is correlational. The results of this study are in line with the research objectives, namely to see whether there is an influence of students' perspectives on mathematics learning integrated with technology. The data shows that there is an influence between students' perspectives on learning mathematics that is integrated with technology.